Results of surgery in patients with bilateral independent temporal lobe spiking (BITLS) with normal MRI or bilateral mesial temporal sclerosis (MTS) investigated with bilateral subdural grids - ARTHUR CUKIERT; ALCIONE SOUSA; ELCIO MACHADO; JOSE AUGUSTO BURATINI; CASSIO FORSTER; MEIRE ARGENTONI (Arquivos de Neuro-Psiquiatria)
PURPOSE: The introduction of new technologies in the clinical practice have greatly decreased the number of patients submitted to invasive recordings. On the other hand, some patients with refractory temporal lobe epilepsy have normal MR scans or bilateral potentially epileptogenic lesions. This paper reports the results of invasive neurophysiology and surgical outcome in such patients. METHOD: Sixteen patients were studied. Eleven had normal MRI (Group I) and five had bilateral mesial temporal sclerosis (Group II). All patients had BITLS and non-localizatory seizures on video-EEG monitoring. All patients were implanted bilaterally with 32-contacts subdural grids. They were submitted to a cortico-amygdalo-total hippocampectomy at the side defined by chronic electrocorticography (ECoG). RESULTS: In Group I, seizures came from a single side in nine patients. In nine patients, seizures started at one side, spread to the ipsolateral contacts and contralaterally afterwards. On the other hand, in two Group I patients seizures started in one mesial region and spread to the contralateral parahippocampus and neocortex before spreading to ipsolateral contacts. All patients in Group II had seizures starting unilaterally with focal EcoG onset in the mesial regions. Eight Group I patients are seizure-free and three are in Engel's class II. Eighty percent of Group II patients are seizure-free after surgery and one patient is in Engel's class II. CONCLUSION: Good surgical results can be obtained in patients with BITLS. Patients with normal MRI seem to have a worse prognosis when compared to patients with unilateral or even bilateral MTS. Extensive subdural coverage is essential in patients with normal MRI.